2007
DOI: 10.1002/uog.3925
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester treatment of fetal anemia secondary to parvovirus B19 infection

Abstract: Here we report two cases of first-trimester parvovirus B19 CASE REPORTS Case 1A 32-year-old primigravida was referred to our unit after routine ultrasound examination revealed increased fetal nuchal translucency (NT) at 13 + 1 weeks' gestation. A detailed sonographic evaluation demonstrated an NT of 4.4 mm, biventricular myocardial hypertrophy, moderate skin edema, mild ascites and bilateral pleural effusion. The ductus venosus (DV) blood flow was normal (positive awave, pulsatility index for veins (PIV): 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 17 publications
0
22
0
3
Order By: Relevance
“…The baseline characteristics of these women are summarized in Table 1. Ten women were noted to have had at least one previous stillbirth as a result of alloimmunization at a median gestational age of 24 weeks (range, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Of this cohort, 26 (87%) were associated with anti-D, four (13%) with anti-Kell and 12 had more than one antibody type involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline characteristics of these women are summarized in Table 1. Ten women were noted to have had at least one previous stillbirth as a result of alloimmunization at a median gestational age of 24 weeks (range, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Of this cohort, 26 (87%) were associated with anti-D, four (13%) with anti-Kell and 12 had more than one antibody type involved.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrops rarely appears before 17 weeks of gestation, probably because of the immaturity of the reticuloendothelial system 4 . Therefore, at early gestation, even in the absence of hydrops, an aggressive approach should be used in establishing the diagnosis of fetal anemia based on the MCA-PSV values, which has been shown to be a helpful diagnostic tool, even in the first trimester 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature in a total of 82 studies involving 705 cases of fetal parvovirus infection showed a clear benefi t of active intervention with IUT over conservative management (82 % vs. 55 % survival rates); also, the signs of anemia usually resolve after a single transfusion [84] . Interestingly, successful management of fetal anemia secondary to parvovirus B19 infection with intravascular transfusion at 13 weeks ' gestation has been reported in two fetuses [36] . Each fetus received a 3-mL intravenous transfusion of packed red blood cells into the umbilical vein, using a 25-gauge spinal needle.…”
Section: Iut In Other Diseasesmentioning
confidence: 99%
“…is associated with poor pregnancy outcome (cardiac and other anomalies, perinatal deaths) and should be regarded as an additional risk factor warranting close ultrasound surveillance Oh et al, 2007;Maiz et al, 2008b). Infection screening should not be routinely performed (Sebire et al, 1997), but it may be appropriate when NT enlargement evolves in the second trimester into an increased nuchal fold, generalized edema, or unexplained hydrops or in women with young children who have been recently ill or have been ill themselves (Markenson et al, 2000;Kempe et al, 2007).…”
Section: Management Of Euploid Fetuses With Increased Ntmentioning
confidence: 99%